Effectiveness and Safety of Polydioxanone Thread Embedding Acupuncture Compared with Acupuncture Treatment for Knee Osteoarthritis: a Protocol for a Pilot, Assessor-Blinded, Randomized Controlled Trial - Hyun Jin Jang; Chang-Hyun Han; Ju Hyun Jeon; Jeong Kyo Jeong; HuiYan Zhao; Changsop Yang; Bok-Nam Seo; Ojin Kwon; WenShan Sun; JinChuan Ran; Hong Xu; Young Il Kim (Journal of Acupuncture & Meridian Studies)
Importance: Knee osteoarthritis (OA) is a common degenerative joint disease in aging populations. Knee OA is difficult to cure and requires ongoing management. Thread embedding acupuncture (TEA) is a popular Korean medical treatment for knee OA. However, clinical evidence of its effectiveness and safety is insufficient. Objective: This study aims to evaluate the effectiveness and safety of TEA compared with acupuncture for knee OA. Design, Setting, and Population: A two-group, two-arm, parallel, single-center, randomized, controlled, and assessor-blinded pilot trial will be conducted. A total of sixty patients aged between 40 and 85 years old will be recruited. Exposures: The TEA group will receive four sessions of TEA treatment over 4 weeks. The acupuncture group will receive eight sessions of acupuncture treatment over 4 weeks. A follow-up assessment will be conducted in week 8 for both groups. Main Outcomes and Measures: Assessments will be performed at baseline, 2 weeks, 4 weeks, and 8 weeks. The primary outcome will be the mean change in the visual analog scale between the two groups at 4 weeks. The secondary outcomes will be the mean change in the Korean Western Ontario and McMaster Universities Osteoarthritis Index, knee range of motion, EuroQol 5-Dimension, patient global impression of change, and dosage of rescue medication. Statistical analysis will be conducted and the level of significance will be achieved in each variables. Results: The results will be published in a peer-reviewed journal. Conclusions and Relevance: This study provides a rationale for the effectiveness and safety of TEA for knee OA by comparing TEA treatment with acupuncture.